Analysis of Factors Influencing Consumer Behavior at Dobo Market, Aru Islands Regency - Harti Oktarina; Sitti Hajar Aswad; Frans Furngilii (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of modern markets and the digitalization of trade have influenced consumer consumption patterns, including in island regions (Kotler Keller, 2016). This study aims to analyze the influence of cultural, social, personal, and psychological factors on consumer behavior at Dobo Market, Aru Islands Regency. The research employed a quantitative approach using a survey method involving 50 consumers. Data were collected through questionnaires that had been tested for validity and reliability, and were subsequently analyzed using multiple linear regression.The results indicate that partially and simultaneously, cultural, social, personal, and psychological factors have a positive and significant effect on consumer behavior. The coefficient of determination value of 96.5% shows that consumer behavior is strongly influenced by the combination of internal and external factors